Catalytic N–Si coupling as a vehicle for silane dehydrocoupling via α-silylene elimination12. Issue 7 (24th January 2018) - Erickson, Karla A.; Cibuzar, Michael P.; Mucha, Neil T.; Waterman, Rory
Abstract : Zirconium compounds appear to promote the liberation of silylene fragments via an N–Si coupling event. Abstract : Exploration of (N3 N)ZrNMe2 (1, N3 N = N(CH2 CH2 NSiMe3 )3 3– ) as a catalyst for the cross-dehydrocoupling or heterodehydrocoupling of silanes and amines suggested silylene reactivity. Further studies of the catalysis and stoichiometric modeling reactions hint at α-silylene elimination as the pivotal mechanistic step, which expands the 3p elements known to engage in this catalysis and provides a new strategy for the catalytic generation of low-valent fragments.